Pengaruh Uu Cipta Kerja (Omnibus Law) pada Kesejahteraan Pekerja Perempuan - Muhamad Rizal (Jurnal Sekretaris dan Administrasi Bisnis, 2021)
On October 5 2020, in a plenary session, the DPR passed a new law, namely the Omnibus Law, the Job Creation Law with the aim of updating the old existing Law. The purpose of writing this journal is to find out what are the impacts on workers, especially women workers. The method of writing this journal is using descriptive method with literature study techniques. Following the enactment of the Job Creation Law, there are several things that are of course detrimental to various parties, for example women workers and laborers. In the implementation process, the Job Creation Law makes women workers uneasy. Therefore, the government should review this law which is considered imperfect. So that neither party will be harmed later.